The Gut Microbiota in the Pathogenesis and Therapeutics of Inflammatory Bowel Disease - Zuo, Tao; Ng, Siew C. (Frontiers in Microbiology, 2018)
In the twenty first century, the changing epidemiology of inflammatory bowel disease (IBD) globally with increasing disease incidence across many countries relates to the altered gut microbiota, due to a combinatorial effect of environmental factors, human immune responses and genetics. IBD is a gastrointestinal disease associated with a gut microbial dysbiosis, including an expansion of facultative anaerobic bacteria of the family Enterobacteriaceae. Advances in high-throughput sequencing enable us to entangle the gut microbiota in human health and IBD beyond the gut bacterial microbiota, expanding insights into the mycobiota, virobiota and helminthes. Caudovirales (viruses) and Basidiomycota, Ascomycota, and Candida albicans (fungi) are revealed to be increased in IBD. The deconvolution of the gut microbiota in IBD lays the basis for unveiling the roles of these various gut microbiota components in IBD pathogenesis and being conductive to instructing on future IBD diagnosis and therapeutics. Here we comprehensively elucidate the alterations in the gut microbiota in IBD, discuss the effect of diets in the gut microbiota in relation to IBD, and illustrate the potential of manipulation of gut microbiota for IBD therapeutics. The therapeutic strategy of antibiotics, prebiotics, probiotics and fecal microbiota transplantation will benefit the effective application of precision microbiome manipulation in IBD.